Tattoo discrimination in Mexico motivates interest in tattoo removal among structurally vulnerable adults - Ojeda, Victoria D.; Magana, Christopher; Shalakhti, Omar; Vargas-Ojeda, Adriana Carolina; Burgos, Jose Luis (Frontiers in Public Health, 2022)
Tattoos are less prevalent in Mexico and tattooed persons are frequently stigmatized. We examine the prevalence and correlates of interest in receiving tattoo removal services among 278 tattooed Mexican adults living in Tijuana, Mexico who responded to interviewer-administered surveys, including open-ended questions. Overall, 69% of participants were interested in receiving free tattoo removal services, 31% reported facing employment barriers due to their tattoos, and 43% of respondents regretted or disliked some of their tattoos. Having a voter identification card, reporting moderate/severe depression symptoms and believing that tattoo removal would remove employment barriers were independently associated with interest in tattoo removal. Our findings suggest that there is substantial interest in tattoo removal services. Publicly financed tattoo removal services may help disadvantaged persons gain access to Mexico's labor market and it may positively impact other life domains such as mental well-being and interactions with law enforcement.